Evalution of cutting sizes and deviated angles on performance of stabilized foam-based mud in cuttings lifting - Amierul Amran, 1989-, author; Issham Ismail, supervisor; Fakulti Kejuruteraan Petroleum dan Kejuruteraan Tenaga Diperbaharui (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper Sarjana Muda Kejuruteraan (Petroleum) - Universiti Teknologi Malaysia, 2012